Kiswahili Language Assistance for Science Students Academic Achievement in a Multilingual Classroom Setting in East Africa: A Study of Government-Aided Western Ugandan Secondary Schools - Lucy Aja; Tukur Muhammad; Keneth Bwema; Mohammad Lubega (Journal of Research in Education and Pedagogy, 2025)
This study investigates the impact of Kiswahili language assistance on academic achievement in science among students in a multilingual classroom setting in East Africa. The study used a quasi-experimental method to statistically evaluate the impact of Kiswahili language assistance on science students’ academic achievement, utilizing a pretest-posttest non-equivalent control group research design. One hundred and eighty randomly selected senior four secondary school students from two schools in western Uganda were given a science achievement multiple-choice question with 60 multiple-choice items to gather data. Pretest and post-test scores were compared using descriptive statistics, and the hypotheses were tested using Analysis of Covariance (ANCOVA) at a significance level of 0.05. The findings reveal that male students performed better than female students when taught using Kiswahili assistance. Similarly, students who were taught science using the Kiswahili language as assistants achieved greater academic achievement in science than those who were taught science using the English Language. These results recommend that Kiswahili language assistance enhances science learning compared to English. Based on the conclusion of these findings, the researchers recommended that teachers should use Kiswahili as a language assistance in the teaching of science to improve student understanding of science concepts. Furthermore, the study also recommends further research on the utilization of language assistance and science learning in the context of multilingualism to inform educational policy and practice.